Loyalty schemes in retailing : a comparison of stand-alone and multi-partner programs - Hoffmann, Nicolas, 1983- (Forschungsergebnisse der Wirtschaftsuniversität Wien, 2013)
To expand existing literature on loyalty schemes, the impact of stand-alone vs. multi-partner programs on customer loyalty was evaluated. In addition, the effects of store satisfaction, membership in competing programs, as well as various shopper characteristics were tested. Therefore, interviews were conducted with loyalty executives and a survey was carried out with 1,150 German customers of two fuel station chains. Stand-alone programs were found to outperform multi-partner schemes in their ability to trigger behavioral loyalty (e.g. share-of-wallet), attitudinal loyalty, and positive word-of-mouth. While program members showed significantly higher levels of loyalty than non-members, those of the stand-alone solution did so to an even greater extent than those of the coalition scheme."Best Dissertation of 2011" by the WU - Vienna University of Economics and Business and Winner of the "Outstanding Award 2011" by the ECR Austria.